Frequency of CCR5 Delta-32 Mutation in Human Immunodeficiency Virus (HIV)-seropositive and HIV-exposed Seronegative Individuals and in General Population of Medellin, Colombia - Francisco J Díaz; Jorge A Vega; Pablo J Patiño; Gabriel Bedoya; Jorge Nagles; Cecilia Villegas; Rodrigo Vesga; Maria T Rugeles (Memorias do Instituto Oswaldo Cruz, 2000)
Repeated exposure to human immunodeficiency virus (HIV) does not always result in seroconversion. Modifications in coreceptors for HIV entrance to target cells are one of the factors that block the infection. We studied the frequency of Delta-32 mutation in ccr5 gene in Medellin, Colombia. Two hundred and eighteen individuals distributed in three different groups were analyzed for Delta-32 mutation in ccr5 gene by polymerase chain reaction (PCR): 29 HIV seropositive (SP), 39 exposed seronegative (ESN) and 150 individuals as a general population sample (GPS). The frequency of the Delta-32 mutant allele was 3.8% for ESN, 2.7% for GPS and 1.7% for SP. Only one homozygous mutant genotype (Delta-32/Delta-32) was found among the ESN (2.6%). The heterozygous genotype (ccr5/Delta-32) was found in eight GPS (5.3%), in one SP (3.4%) and in one ESN (2.6%). The differences in the allelic and genotypic frequencies among the three groups were not statistically significant. A comparison between the expected and the observed genotypic frequencies showed that these frequencies were significantly different for the ESN group, which indirectly suggests a protective effect of the mutant genotype (Delta-32/Delta-32). Since this mutant genotype explained the resistance of infection in only one of our ESN persons, different mechanisms of protection must be playing a more important role in this population.